Análise dinâmica de eixos trincados por meio de emissão acústica - Gilberto Luiz dos Santos Pimentel Junior (2016)
This study was based on the fundamentals of Acoustic Emissions, with emphasis on statistical data analysis and the application of wavelet transform and the fundamentals of rotor dynamics, with emphasis on dynamic response of six axes with presence of transverse cracks which followed a increasing ratio between the values of their depths p and the radius r of the cross section of each axis. The methodology is developed in two ways. In the first analysis acoustic emissions signals were analyzed in six stationary axes. In this mode each axis was suspended for two nylon threads at their ends, given the Free - Free condition. Each axis experienced five beats of a metal rod, which was suspended using an experimental apparatus. Analyses of Skewness 3 and kurtosis 4 of the amplitudes of the Acoustic Emission signals suggest a direct relationship between the decline in values of these statistical indicators and increasing depth p of transverse crack. In the second analysis AE signals were analyzed in six rotary axes supported in hydrodynamic bearings. In this analysis each axis operated at four specific speeds. These speeds were generated by a Dynamic Compact Bench Tests. The decomposition of AE signals through the discrete wavelet transform and the analysis of the Median Absolute Deviation of the amplitude values of these signals suggest a direct relationship between the increase in the value of this statistical indicator and the increasing of the transverse crack depth p.